Nutrient intake and diet quality impacts of a nutrition-sensitive resilience program in Sri Lanka - Caswell, Bess L.; Tan, Xiuping; Joyce, Caroline A.; Arnold, Charles D.; Sitisekara, Hasara; Jayatissa, Renuka; Peiris, Kalana; Silva, Renuka; Olney, Deanna K. (Elsevier, 2024)
Objectives: R5N was an agriculture-based resilience program to strengthen rural farming communities against shocks and to improve livelihoods. It was conducted by the World Food Programme (WFP) and Government of Sri Lanka from 2019 to 2022, with or without an 8-mo health promotion process (HPP). We aimed to assess the impacts of R5N and R5N+HPP on diet quality and nutrient intakes among adults in the program area.